AMARU - Redes de Colaboração em Terapia Ocupacional na América Latina - Passoni, Thayla Gabriele Pereira (Universidade Federal de São Carlos, 2023)
The present work aims to present the analyzes and discussions carried out by the research “AMARU - Collaboration Networks in Occupational Therapy in Latin America”. Its about a documentary, quantitative-qualitative analysis, based on the mapping carried out by AMARU Network, through the online form on the Google Forms® platform, which has seven different sections, aimed at researchers/occupational therapists from America Latin. The objective of the research was to analyze and discuss the organization of forms of networks of collaboration and dissemination of knowledge, practices and projects among therapists Occupational. The first stage of the research was the selection and categorization of the responses of the mapping, seeking to identify information on the use of information sources, networks of work, access to journals and formation of collaboration networks, among other relevant information. The second stage consisted of the primary analysis of the responses, division into thematic axes and interpretation of data derived from the mapping. The search collected 108 responses. An important part of occupational therapists claim to develop group searches (92.6%). The most used sources of information are scientific articles and books on Occupational Therapy and other areas, from Latin America and Anglophone countries. The three most accessed Latin American periodicals are: the “Cadernos Brasileiros de Occupational Therapy” (71%); the “Chilean Journal of Occupational Therapy” (56%); and the “Magazine Brazilian Interinstitutional Association for Occupational Therapy – REVISBRATO” (43%). The main difficulties found for the dissemination of knowledge/work are: the organization and daily work time (66%), publishing in another language (64%) and the financing of publications (61%). All respondents are interested in joining the AMARU Network. You Latin American journals have been important disseminators of knowledge for researchers in the area, also considering the limits of the sample.
AMARU - Collaborative Networks in Occupational Therapy in Latin America
Keywords: Terapia ocupacional; Produção de conhecimento; América Latina; Redes de colaboração; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL